A wireless utility meter system: design and implementation - Al Farabi, Muhammad (2012)
The conventional utility billing system suffers from the inefficiency of utility providers workforce deployment. Apart from the financial cost issue, unnecessary workforce deployment will result in an extensive period of utility meter reading and billing. The solution proposed in the authors Malaysian patents numbered PI2010002408 and PI20100022305 is the utilization of a wireless utility meter system for application of water meter specifically and other utility types, at large. The proposed wireless utility meter system makes use of an onsite utility usage monitoring and billing, that is capable of reducing the utility providers workforce deployment while serving as a necessary transient step towards a truly automatic monitoring and billing solution. Another advantage in the proposed semi-automatic wireless onsite meter reading is the elimination of unnecessary cost of maintaining the complicated fully automatic offsite wireless meter reading. The proposed wireless utility meter system is designed using SKXBee wireless modules. In the proposed design, consideration is also given to the utility usage database system. Indeed, in the near future, the proposed wireless utility meter design can be implemented as a transient step before the application of a fully automatic wireless meter solution becomes feasible in the third world countries.